Immunity of Advocates In The Criminal Investigation Process: Balancing Professional Ethics and Law Enforcement - Bhat, Manoj; Taufik, Moh.; Marwiyah, Siti (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The purpose of this study is to analyze the limits of advocate immunity in the criminal investigation process in Indonesia according to positive law and professional ethics, and to examine efforts to achieve a balance between the protection of the advocate profession and law enforcement through the application of professional ethics. This study uses a normative legal method with a statutory, conceptual, case, historical, and comparative approach through literature studies and descriptive-qualitative analysis of primary, secondary, and tertiary legal materials. The results of the study indicate that advocate immunity in the criminal investigation process in Indonesia is a form of legal protection that is limited and depends on good faith, namely as long as the advocate's actions are carried out professionally, honestly, and in accordance with the law and the professional code of ethics, then he cannot be punished; however, if the advocate exceeds these limits, the advocate can still be held criminally responsible, so that the balance between professional protection and law enforcement can only be achieved through the application of firm, consistent, and adaptive professional ethics as a moral guideline as well as a control mechanism to maintain the integrity of the profession and prevent the abuse of immunity in legal practice